Keefektifan Model Blended Learning terhadap Kemandirian Belajar Peserta Didik SMA IT Albina Kota Ternate - Asmin Lukman; Irfan H. Arif (Jurnal Ilmiah Wahana Pendidikan, 2021)
The aim of this study is to increase student learning independence through a blended learning approach. This research method uses classroom action research approach through two cycles. The research was conducted at SMA IT Albina, Ternate City. The research subjects included 12 students of class XI IPA. Data collection instruments include student learning outcomes tests, learning independence questionnaires, and observation sheets. The results of the research in the first cycle showed that the average observation results obtained 65.97% of students had learning independence. The learning outcomes of students who reach the KKM score are 41.6%. The results of class observations in the second cycle obtained 78,82% of students have learning independence. The learning outcomes of students who reach the KKM score are 83.33%. This research can be concluded that the application of blended learning can increase students' learning independence in the addition and subtraction of matrices, as well as matrix multiplication.